Managing tourism during the COVID-19 pandemic. A systematic review of crisis management in the tourism industry - Foday Yaya Drammeh (Cogent Social Sciences, 2024)
COVID-19 has caused severe economic crises, unemployment, and disruptions to the global tourism industry. This study aims to establish the current body of knowledge on crisis management in tourism published from to 2001–2021, with the objective of providing research avenues on how to manage crises, such as the COVID-19 pandemic. The study shows that crisis management in tourism is based on the survival strategies of the tourism subsectors in Europe, Asia, the USA, and Australia. A universal approach is limited, indicating the immaturity of the research in this area. There is a need to expand the analysis including approaches in Africa and strategies of the tourism subsectors during the COVID-19 pandemic. This knowledge of the local tourism subsectors that focus need to be put upon are limited. The literature is fragmented, lacks precision, and is a common approach that the tourism industry should follow during uncertain situations such as the COVID-19 pandemic. The absence of a theoretical framework on crisis management that is inclusive of what tourism could rely on during such situations is a concern. This study contributes to the framework that tourism researchers, policymakers, and practitioners could rely upon when dealing with crises such as the COVID-19 pandemic.